Chia Seed / Muhammad Fariz Ikmal Abd Rahim - Muhammad Fariz Ikmal, Abd Rahim (2020)
Healthy.Co is a sole proprietorship company, which mean everything are done independently from the beginning which is marketing strategy to the last which is financial plan. A slogan for my company is provide a healthy lifestyle in all range and age. The vision for my company is encourage inner health among the public user by consuming my product. With some help from suitable machineries, a good and healthy drink from chia seed can be made easily. At the same time, my company try to give or serve the customer taste the best quality of chia seed drink at the lowest price in Malaysia and also overseas. Malaysia as a growing fast country and also full of people who are so busy and rushing like students and working people. Most of them did not have much time to get healthy and nutritious food or drink for their life so I believe that my product which is easy to carry can be a solution among the busy people to get their healthy drink. There are one company that already made a product like my company but they are a company from other country. Their product call Basil Chia Seed Drink. So, they are one and only my competitor and also be a source of motivation for all of Healthy.Co team to keep serving people a healthy drink from chia seed. Based on the size of our market area, our sales target for the first year is RM 343,000.00. Then we project growth rate of 5 % per year for the first four years. We have 3 team in the company which are marketing, operation, financial and human resources. These team will make sure all thing go well in their department and try to give the best service in their job scope.